Leptin-Mediated Sympathoexcitation in Obese Rats: Role for Neuron–Astrocyte Crosstalk in the Arcuate Nucleus - Liu, Xuefei; Zheng, Hong (Frontiers in Neuroscience, 2019)
Introduction: Accumulated evidence indicates that enhanced sympathetic activation is associated with obesity. Hypothalamic leptin-mediated signaling may contribute to the exaggerated sympatho-excitation in obesity. The present study was conducted to investigate “neuron-astrocyte” interactions regulating leptin signaling within the arcuate nucleus (ARCN) of hypothalamus in obese rats. Methods and Results: Obesity was induced by high-fat diet (HFD, 42% fat for 12 weeks) in Sprague Dawley rats. We found that leptin receptor was localized in both neurons and astrocytes in the ARCN. In the HFD obese rats, the expression of leptin receptor was increased in the ARCN compared to the normal diet rats. The HFD rats had increased level of glial fibrillary acidic protein (GFAP) in the ARCN. In anaesthetized condition, electrophysiological study showed that microinjections of leptin into the ARCN induced increases in renal sympathetic nerve activity (RSNA), mean arterial pressure (MAP) and heart rate (HR) in both control and HFD rats. Microinjection of leptin elicited significant higher increases in RSNA and MAP in the ARCN in the HFD rats. Pre-inhibition of astrocytes with astrocytic metabolic inhibitor fluorocitrate reduced leptin-induced RSNA, MAP and HR responses within the ARCN. Furthermore, we found that the expressions of astrocyte specific glutamate transporters, excitatory amino acid transporter 1 (EAAT1) and EAAT2 were decreased within the ARCN in the HFD rats. In cultured astrocytic C6 cells, the levels of GFAP, EAAT1 and EAAT2 were significantly changed in response to 24 hours leptin simulation. Conclusion: The results suggested that leptin signaling might be via neuron-astrocyte interactions in the ARCN, contributing to the exaggerated sympatho-excitation observed in obese rats. The effects might be mediated by the action of leptin regulating astrocytic glutamate transporters within the ARCN of the hypothalamus.